2013
DOI: 10.3109/17435390.2012.760014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and biodistribution of aqueous synthesized ZnS and ZnO quantum dots in mice

Abstract: In the present study, ZnS and ZnO quantum dots (QDs) were synthesized via an all-aqueous process with polyethylene glycol (PEG) chains on their surface, and their toxicity as well as biodistribution were evaluated. No haemolysis occurred at a high concentration of 1600 µg/mL in vitro haemolytic assay, which demonstrated that the QDs-PEG displayed good blood compatibility. Following intravenous administration at 2, 6, and 20 mg/kg of the QDs-PEG in mice, the biodistribution, excretion and biocompatibility were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Additionally, our previous study found that ZnS and ZnO QDs were both mainly located in the liver after intravenous injection. 29 The accumulation and metabolism of QDs may cause toxic and other unwanted effects on liver tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our previous study found that ZnS and ZnO QDs were both mainly located in the liver after intravenous injection. 29 The accumulation and metabolism of QDs may cause toxic and other unwanted effects on liver tissue.…”
mentioning
confidence: 99%
“…This result is in accordance with our previous report that ZnS QDs did not cause noticeable toxicity in mice. 29 The levels of serum aminotransferases (ALT and AST) correspond well with the extent of liver cell damage and are commonly used as indicators of liver function. In liver cells, ALT is mainly found in the cytoplasm and is sensitive to acute hepatocyte injury induced by drugs or alcohol.…”
mentioning
confidence: 99%
“…Some previous evidence also indicated that PEG capped QDs presented good blood compatibility, and tended to attenuate the toxicity of uncoated QDs with different core/ shell materials by inhibiting ROS generation Zhang et al, 2013). However, Ho et al (2013) suggested that PEG coatings failed to prevent adverse responses caused by administration of QDs via the lung, where they were mainly trapped in the lung and needed a few time to be removed (Yang et al, 2013). Otherwise, PEG is still useful for minimizing the toxicity of other nanoparticles (Ju et al, 2013).…”
Section: Outer Coatingmentioning
confidence: 91%
“…PEGylated QDs have also been successfully produced for effective in vitro and in vivo circulation (Skaff and Emrick, 2003; Hu et al, 2010; Prow et al, 2012; Yang et al, 2012b). Recently, Poulose et al developed highly biocompatible PEG functionalized in cadmium chalcogenide luminescent QDs (CdS, CdSe, and CdTe) as an imaging tool for early diagnosis of cancer by targeting a cancer cell line (Poulose et al, 2012).…”
Section: Biofunctionalization Of Inorganic Nanoparticlesmentioning
confidence: 99%